Influence of veil interleave distribution on the delamination resistance of cross-ply CFRP laminates under low velocity impact. (November 2021) - Ramji, Amit; Xu, Yigeng; Yasaee, Mehdi; Grasso, Marzio; Webb, Philip
Abstract: This paper focuses on the influence of polyphenylene sulfide (PPS) veil distribution within unidirectional carbon fibre reinforced polymer (CFRP) laminates under low velocity impact (LVI). Tests were conducted on a baseline layup of (0/90)7s, modified with various levels of veil interleaving at the middle or the outer plies. The results demonstrate that veil interleaving can reduce and migrate the damage from predominantly inter-laminar to intra-laminar for veils positioned in the outer plies. The interleaved configurations also display differences in the impact stiffness [1] after the Delamination Threshold Load (DTL), implying the level of damage is lower than those with fewer veils and those positioned at the mid-level neutral plane. Interesting changes in the impact force history are also observed where a smoothing effect around the DTL is achieved through interleaving. Fracture migration effects are also considered and provide a significant insight into the damage characteristics when using CFRP laminates with interleaved PPS veils under LVI. Graphical abstract: Image, graphical abstract